Efektivitas Pemerintah Daerah dalam Kebijakan Pembangunan Infrastruktur dan Taman Kota sebagai Ruang Publik Multifungsi di Bundaran Besar Palangkaraya - Rosa Nadaeva; Putri Marcela; Rira Kristiana; Rendy Stalar (Fakultas Teknik Universitas Cenderawasih, 2026)
This study examines the effectiveness of local government policies in infrastructure development and urban park management as multifunctional public spaces at Bundaran Besar Palangkaraya. Rapid urban development and increasing community needs for public spaces have encouraged the government to revitalize this area as a city landmark and social interaction space. This study uses a qualitative descriptive method with data collection techniques through literature review, observation, and documentation. The results show that the development and revitalization of Bundaran Besar have improved aesthetic quality, public facilities, environmental conditions, and social functions. However, several challenges remain, including limited accessibility for certain groups, suboptimal management and maintenance systems, and traffic and parking issues during peak hours. The analysis indicates that although government policies have contributed positively to the development of public spaces, their effectiveness is still not fully optimal. Therefore, stronger governance, community participation, and sustainable management strategies are needed to enhance the role of Bundaran Besar as an inclusive, functional, and sustainable public space.